National survey of US primary care physicians’ perspectives about causes of obesity and solutions to improve care - Wendy L Bennett; Sara N Bleich; Kimberly A Gudzune; Lisa A Cooper (BMJ Open)
Objective To describe physician perspectives on the causes of and solutions to obesity care and identify differences in these perspectives by number of years since completion of medical school.Design National cross-sectional online survey from 9 February to 1 March 2011.Setting USA.Participants 500 primary care physicians.Main Measures We evaluated physician perspectives on: (1) causes of obesity, (2) competence in treating obese patients, (3) perspectives on the health professional most qualified to help obese patients lose or maintain weight and (4) solutions for improving obesity care.Results Primary care physicians overwhelmingly supported additional training (such as nutrition counselling) and practice-based changes (such as having scales report body mass index) to help them improve their obesity care. They also identified nutritionists/dietitians as the most qualified providers to care for obese patients. Physicians with fewer than 20 years since completion of medical school were more likely to identify lack of information about good eating habits and lack of access to healthy food as important causes of obesity. They also reported feeling relatively more successful helping obese patients lose weight. The response rate for the survey was 25.6%.Conclusions Our results indicate a perceived need for improved medical education related to obesity care.